The Succession of Bacterial Community Attached on Biodegradable Plastic Mulches During the Degradation in Soil - Ju, Zhicheng; Du, Xiongfeng; Feng, Kai; Li, Shuzhen; Gu, Songsong; Jin, Decai; Deng, Ye (Frontiers in Microbiology, 2021)
Abstract: Despite the increasing application of biodegradable plastic mulches in agriculture, the colonization and succession of the attached microbial community on BDMs during their degradation processes remain poorly characterized. Here, we buried four types of commonly used BDMs, including pure polylactic acid, pure polybutylene adipate terephthalate, and two mixtures of PLA and PBAT (85:15 and 15:85 w/w), and a classic polyethylene (PE) mulch in soil for 5 months. The morphological characteristics of these mulches displayed obvious degradations in all BDMs and just some minor changes in PE mulch at the end of incubation. Both plastic components and incubation time significantly shaped the β-diversities of microbiota on the plastic mulches (P<0.001). Meanwhile, the microbial compositions and community structures on BDMs were significantly different from PE mulch, and when excluding PE mulch, the microbiota varied more with time than by the composition of the four BDMs. The orders Burkholderiales and Pseudonocardiales were dominant on most BDMs across different time points, with the genus Ramlibacter revealed as the common biomarker for both PLA and PBAT by random forest model, and all biomarkers for the BDMs belonged to the dominant order Burkholderiales. In addition to the detected functions belonging to carbon, nitrogen, and sulfur metabolisms, degradation-related and pathogen-related functional taxa were enriched in all mulches among the forty functional groups, while surprisingly, potential pathogens were detected at higher levels on BDMs than PE mulch. Moreover, for community assembly on all mulches, the drift and dispersal processes played more important roles than selection, and in particular the contribution of stochastic drift increased during the degradation process of BDMs while selection decreased, the opposite trend was observed with PE mulch. Overall, our results demonstrated some degradation species and pathogens were especially enriched on BDMs, though stochastic processes also had important impacts on the community assembly on these agricultural mulches. It suggested that, similar to conventional plastic mulch, the increased usage of BDMs could lead to potential hazards to crops and human health.